2017
DOI: 10.1002/ceat.201600419
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption and Binding Mechanisms of Ni2+ and Cd2+ with Aerobic Granules Cultivated in Different Synthetic Media

Abstract: Aerobic granules synthesized by feeding real wastewater (R‐granules) in a sequencing batch reactor were applied to remove Ni2+ and Cd2+ from aqueous solutions and compared with granules cultivated with laboratory‐synthesized wastewater (S‐granules). Metal biosorption was related to solution pH, initial metal concentration, and reaction time. The chemically modified R‐granules showed increased removal efficiency for the examined metals, and the results were almost identical to those of S‐granules. Ion‐exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…FI-IR spectroscopy evidenced that anammox EPS were rich in potential metal-binding sites (e.g., amine and carboxyl groups), disclosing a role of protein-and polysaccharide-like substances in the heavy metal uptake (i.e., significant shifts of the corresponding peaks were detected in the FT-IR spectra of EPS samples after heavy metal sorption, as described more detailed in Figure S4 in Supplementary material). In agreement with the literature, reporting the ion exchange as a common mechanism to describe the metal biosorption by EPS (Li and Yu, 2014) and/or biomass (Sajjad et al, 2017), the heavy metal uptake by anammox EPS and granules was associated to releases of alkali and alkaline earth metal ions (e.g., Ca 2+ , Na + , Mg 2+ and K + ) into the liquid bulk, resulting from a relatively lower affinity and competitiveness of the exchangeable cations to bind with the sorbent (Wang et al, 2010). Figure 4 biosorption, respectively), with a lower amount of K + (5.7, 5.8, 24.1 and 6.7% of the total metal ion release for Pb 2+ , Cu 2+ , Ni 2+ and Zn 2+ biosorption, respectively) detected in the aqueous medium after biosorption.…”
Section: Biosorption Mechanismssupporting
confidence: 90%
See 1 more Smart Citation
“…FI-IR spectroscopy evidenced that anammox EPS were rich in potential metal-binding sites (e.g., amine and carboxyl groups), disclosing a role of protein-and polysaccharide-like substances in the heavy metal uptake (i.e., significant shifts of the corresponding peaks were detected in the FT-IR spectra of EPS samples after heavy metal sorption, as described more detailed in Figure S4 in Supplementary material). In agreement with the literature, reporting the ion exchange as a common mechanism to describe the metal biosorption by EPS (Li and Yu, 2014) and/or biomass (Sajjad et al, 2017), the heavy metal uptake by anammox EPS and granules was associated to releases of alkali and alkaline earth metal ions (e.g., Ca 2+ , Na + , Mg 2+ and K + ) into the liquid bulk, resulting from a relatively lower affinity and competitiveness of the exchangeable cations to bind with the sorbent (Wang et al, 2010). Figure 4 biosorption, respectively), with a lower amount of K + (5.7, 5.8, 24.1 and 6.7% of the total metal ion release for Pb 2+ , Cu 2+ , Ni 2+ and Zn 2+ biosorption, respectively) detected in the aqueous medium after biosorption.…”
Section: Biosorption Mechanismssupporting
confidence: 90%
“…To evaluate the effect of the initial heavy metal concentration (C0, mg/L) on biosorption, heavy metal solutions (4 mL) with concentrations ranging between 10 and 1000 mgM 2+ /L were mixed anammox EPS dispersions (4 mL, 12.95 ± 1.65 gTSEPS/L) in separate flasks and kept in contact under stirred conditions (120 rpm) at a temperature of 20 ± 0.5 °C for 6 hours. Based on the information available in literature (Liu et al, 2015;Wei et al, 2016;Sajjad et al, 2017) and on preliminary kinetic studies (Figure S2 in Supplementary material), a contact time of 6 hours was considered as sufficient to attain sorption equilibrium. The pH of the mixed EPS-heavy metal aqueous systems was adjusted to 5.0 (for Pb 2+ and Cu 2+ ) -6.0 (for Zn 2+ and Ni 2+ ) by adding 0.1 M HCl and NaOH aqueous solutions, in order to avoid precipitation of metal salts.…”
Section: Heavy Metal Biosorption Studies With Anammox Epsmentioning
confidence: 99%
“…Recent studies have shown that the strains isolated from polluted environments have greater resilience to metals and are more effective in decontamination processes (Malik, 2004). Additional advantages are the in situ self-production of adsorbent biomass and better results when real leachates are used (Malik, 2004;Sajjad et al, 2017). On the other hand, biofilms allow for simultaneous decontamination of a wide variety of contaminants, including organic matter, nitrates, sulfates, organic compounds, metals, etc.…”
Section: Introductionmentioning
confidence: 99%